Apixaban and rivaroxaban anti-Xa level utilization and associated bleeding events within an academic health system. Issue 196 (December 2020) - Jakowenko, Nicholas; Nguyen, Steffany; Ruegger, Melanie; Dinh, Ashley; Salazar, Eric; Donahue, Kevin R.
Abstract: Background: Oral factor Xa inhibitors (FXaI) can be administered in fixed doses without the need for routine laboratory monitoring. Anti-Xa assays can estimate anticoagulant effect for specific FXaI's. The aim of this study was to characterize anti-Xa levels in patients taking apixaban or rivaroxaban with major bleeding events. Methods: Apixaban and rivaroxaban anti-Xa assays ordered within our hospital system from May 2016 to September 2019 were evaluated. The primary outcome was major bleeding events defined by International Society of Thrombosis and Haemostasis criteria. Median anti-Xa levels for each FXaI were calculated for those with and without major bleeding, as well as those who did and did not receive reversal agents. Results: A total of 606 anti-Xa levels were analyzed. There were 146 major bleeding events documented, with the most common site being intracranial (63%). Median anti-Xa levels in patients with and without major bleeding were similar, whereas those on apixaban therapy who received reversal agents typically had higher anti-Xa levels (73 ng/mL vs. 153 ng/mL, p = 0.0019). Factors significantly associated with increased odds of bleeding were an age > 80 years, inappropriately high dosing regimens, and modest anti-Xa levels (100–300 ng/mL) for rivaroxaban specifically. Conclusions: Older age and inappropriately high dosing regimens were associated with major bleeding in patients taking apixaban and rivaroxaban. Further investigation into the utility of anti-Xa levels for FXaI is warranted. Highlights: Quantification and assessment of anticoagulation can be accomplished with factor Xa inhibitor (FXaI) specific anti-Xa levels Elderly patients and those on inappropriately high dosing regimens may be at an elevated risk for major bleeding It is unclear if elevated anti-Xa levels confer a direct increased risk for bleeding in the absence of other factors Anti-Xa levels are useful for confirmed or suspected bleeding, clearance for parenteral anticoagulation, and prior to an emergent procedure